Architecture and the language debate : artistic and linguistic exchanges in early modern Italy - Temple, Nicholas (Abingdon, Oxon ; New York : Routledge, 2020)
"This book examines the creative exchanges between architects, artists and intellectuals, from the Early Renaissance to the beginning of the Enlightenment, in the forging of relationships between architecture and emerging concepts of language in early modern in Italy. The study extends across the spectrum of linguistic disputes during this time - among members of the clergy, humanists, philosophers and polymaths - on issues of grammar, rhetoric, philology, etymology and epigraphy, and how these disputes paralleled and informed important developments in architectural thinking and practice. Drawing upon a wealth of primary source material, such as humanist tracts, philosophical works, architectural/antiquarian treatises, epigraphic/philological studies, religious sermons and grammaticae, the book traces key periods when the emerging field of linguistics in early modern Italy impacted on the theory, design and symbolism of buildings"--
La Sapienza and the Aristotelian dispute -- Conclusion -- Notes -- 4. Pastoral language in the early eighteenth century (Arcadianism) -- Republic of Letters -- History and ethos of the Arcadians -- Design and iconography of the Accademia degli Arcadi -- The Palazzo Corsini and the architecture of 'buon gusto' -- St. Eustachio and the ethos of early Christian architecture -- Architecture contests and theatre performances among the Arcadians -- Conclusion -- Notes -- Conclusion -- Notes -- Select bibliography -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Communication in architecture -- Italy -- History; Architecture and society -- Italy -- History; Linguistics -- Italy -- History; ARCHITECTURE / General